2020
DOI: 10.7556/jaoa.2020.134
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Musculoskeletal Disorders in Chronic Disease: A Narrative Review

Abstract: Chronic diseases and musculoskeletal conditions are responsible for a significant portion of the global disease burden and are frequently comorbid, such as with low back pain in patients who also have chronic organ disease. Low back pain is the leading cause of long-term disability and is the most common reason adults seek adjunctive treatment, including osteopathic manipulative treatment (OMT). OMT has been shown to be effective in relieving low back pain and improving back-specific functioning. In this narra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This observation supports the notion that anatomically diffuse, OMT-refractory SD represents a neuromusculoskeletal complication of SFR that, to date, has not been described in the medical literature. Anatomically diffuse, OMT-refractory SD may, therefore, possibly serve as a marker of underlying systemic disease, such as in the current setting of vasculitis due to SFR or as previously reported in patients with diabetes mellitus [ 18 ].…”
Section: Discussionmentioning
confidence: 89%
“…This observation supports the notion that anatomically diffuse, OMT-refractory SD represents a neuromusculoskeletal complication of SFR that, to date, has not been described in the medical literature. Anatomically diffuse, OMT-refractory SD may, therefore, possibly serve as a marker of underlying systemic disease, such as in the current setting of vasculitis due to SFR or as previously reported in patients with diabetes mellitus [ 18 ].…”
Section: Discussionmentioning
confidence: 89%
“…Dysfunction in the musculoskeletal system can ultimately affect systemic function. Treating somatic dysfunction could decrease the risk and symptoms of other chronic diseases, such as diabetes mellitus [ 4 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this hands-on manipulation is to restore one’s natural function by allowing various aspects such as cardiovascular, respiratory, circulatory, musculoskeletal, and neurological systems to work together in unity [ 3 , 4 ]. It has been well demonstrated that OMM not only can serve as alternative, complementary, or facilitated treatment but also function as a direct treatment for human disorders such as pneumonia [ 5 , 6 ], low back pain [ 7 - 9 ], and musculoskeletal dysfunctions [ 4 , 10 ]. Although OMM is widely recognized both within the United States (US) and internationally, there has been controversy regarding the efficacy of OMM due to limited documentation of clear mechanisms of action, the quality of experimental designs, and the limited amount of evidence shown in the scientific literature [ 1 , 2 , 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation